The mobile vaccine equity enhancement program–a model program for enhancing equity in vaccine availability based at a large health care system - Broach, John; Brown, Olga; McEachern, Caitlin; Forget, Janell; Lancette, Peter; Soucie, Norman; Inzerillo, Julie; Klugman, Robert; Tosi, Stephen; Haddad, Abraham; Manor, Pamela; Bylund, Richard; et al. (Frontiers in Public Health, 2023)
The SARS CoV-2 (COVID-19) pandemic presented unprecedented challenges as communities attempted to respond to the administration of a novel vaccine that faced cold chain logistical requirements and vaccine hesitancy among many, as well as complicated phased rollout plans that changed frequently as availability of the vaccine waxed and waned. The COVID-19 pandemic also disproportionately affected communities of color and communities with barriers to accessing healthcare. In the setting of these difficulties, a program was created specifically to address inequity in vaccine administration with a focus on communities of color and linguistic diversity as well as those who had technological barriers to online sign-up processes common at mass vaccination sites. This effort, the Mobile Vaccine Equity Enhancement Program (MVeeP), delivered over 12,000 vaccines in 24 months through a reproducible set of practices that can inform equity-driven vaccine efforts in future pandemics.